The Effect of Results Share System, Diversity of Services Products, Completeness of ATM Facilities on Customer Satisfaction of Sharia Mandiri Bank in Mataram City - Irwan Suriadi; Himawan Sutanto; M. Mujahid Dakwah (East Asian Journal of Multidisciplinary Research, 2022)
The research objectives are (a) to find out which of the variables of the profit sharing system, the diversity of service products and the completeness of ATM facilities affect the satisfaction of Mandiri sharia bank customers in the city of Mataram, (b) to find out what variables are the most dominant influencing Mandiri sharia bank customer satisfaction. in Mataram City. The data collection method used in this research is a survey method by distributing questionnaires randomly to muamalat bank customers and Mandiri sharia bank customers in the city of Mataram with a total of 60 respondents in 2020, to test the quality and validity of the questionnaire data used for validity and data reliability tests. The data analysis technique used in this research is multiple regression analysis with the help of SPSS software. The results of this study are the variables that affect customer satisfaction of Mandiri Islamic banks in the city of Mataram are the variables of service product diversity and the completeness of facilities (ATM) variables while the most dominant variable affecting the satisfaction of Mandiri sharia bank customers in the city of Mataram is completeness of facilities (ATM).